2022
DOI: 10.31234/osf.io/ts76y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Counterfactuals and the logic of causal selection

Abstract: Everything that happens has a multitude of causes, but people make causal judgments effortlessly. How do people select one particular cause (e.g. the lightning bolt that set the forest ablaze) out of the set of factors that contributed to the event (the oxygen in the air, the dry weather. . . )? Cognitive scientists have suggested that people make causal judgments about an event by simulating alternative ways things could have happened. We argue that this counterfactual theory explains many features of human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 87 publications
3
15
0
Order By: Relevance
“…The current research is informed by counterfactual theories of causal judgment (Gerstenberg, Goodman, Lagnado, & Tenenbaum, 2021; Lewis, 1973; Lucas & Kemp, 2015; Mackie, 1974; Quillien & Lucas, 2023; Woodward, 2005). According to this view, people determine causality by comparing the actual, known outcome to a counterfactual that informs what would have happened if the candidate cause had been absent.…”
Section: The Present Researchmentioning
confidence: 99%
“…The current research is informed by counterfactual theories of causal judgment (Gerstenberg, Goodman, Lagnado, & Tenenbaum, 2021; Lewis, 1973; Lucas & Kemp, 2015; Mackie, 1974; Quillien & Lucas, 2023; Woodward, 2005). According to this view, people determine causality by comparing the actual, known outcome to a counterfactual that informs what would have happened if the candidate cause had been absent.…”
Section: The Present Researchmentioning
confidence: 99%
“…However, when both player C and D succeeded, then the team would have won even if player C (or D) had failed. Lagnado et al (2013) found that both criticality and pivotality were important for capturing participants' responsibility judgments (see also Quillien & Lucas, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Within this framework, ex-post responsibility is constructed as a function of both ex-ante criticality and ex-post pivotality. A combination of criticality and pivotality explains responsibility attributions better than each component separately (see also Quillien & Lucas, 2022). To test the criticality-pivotality framework, we used several formalizations of criticality, which we termed the anticipated pivotality model, the heuristic model and the necessity model (Lagnado, Gerstenberg, & Zultan, 2013, p. 1054-1056.…”
Section: Introductionmentioning
confidence: 99%